Peran Guru PAI Dalam Mengatasi Kesulitan Belajar Siswa Pada Pembelajaran PAI - Jaka Nugraha (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
This research was motivated by the learning difficulties of students in school. The purpose of this study was to find out what roles PAI teachers play in overcoming student learning difficulties in PAI learning. This research was conducted at SMP Negeri 1 Ciwidey with a qualitative approach descriptive method Data collection techniques using interviews, observations and documentation studies. The results of this study show that the learning difficulties experienced by students are low student interest in PAI subjects, there is no motivation in students to learn PAI material, lazy to study, skip school, difficult to understand the material, difficult to do assignments, low learning outcomes. The role of teachers in overcoming student learning difficulties is educators, teachers, and evaluators. The role of teachers is developed into 10 roles of EMASLIMDEF (Educator, Manager, Administrator, Supervisor, Leader, Innovator, Motivator, Dynamicator, Evaluator, Facilitator).